Chemical profile and bioactive properties of the essential oil isolated from Ammodaucus leucotrichus fruits growing in Sahara and its evaluation as a cosmeceutical ingredient - Halla, Noureddine (2018)
Ammodaucus leucotrichus is a medicinal plant commonly used in Algeria by the indigenous populations, especially due to its therapeutic effects. In this context, the aim of the present study was to chemically characterize the essential oil of A. leucotrichus fruits (EOALF) growing in Algerian Sahara, and to evaluate its bioactive properties (antimicrobial, antioxidant and anti-inflammatory). Considering the interest of the cosmetic industry for natural ingredients, and taking into account the obtained biological properties, the essential oil was also evaluated by incorporation in a base cosmetic (cream). The essential oil was extracted with a yield of 2.58 ± 0.17%, being perilla aldehyde identified as the main component, accounting for 85.6% of the total composition. Concerning the tested bioactivities, EOALF presented antioxidant potential, a strong anti-inflammatory activity, and was effective against the tested microbial strains (Staphylococcus aureus, Eschericia coli and Pseudomonas aeruginosa), being S. aureus the most sensitive bacteria. After incorporation in a base cosmetic, the developed formulation was able to preserve the EOALF bioactivities along 28 days under storage. The obtained results, with relevance for the strong-anti-inflammatory activity, pointed out the interest to exploit this essential oil as a cosmeceutical ingredient in the cosmetic industry.